Adsorption analysis of PFOA on activated carbon and ion-exchange resin: A comparative study using four isotherm models - Kasalica Kristina B.; Petronijević Natalija; Radulović Jelena; Slavković Beškoski Latinka; Lješević Marija B.; Marković Bojana; Beškoski Vladimir P. (Journal of the Serbian Chemical Society)
Per- and polyfluoroalkyl substances (PFAS), known as “forever chemicals”, are highly persistent environmental pollutants due to their strong carbon–fluorine bonds. Widely used across industries and consumer products, PFAS have accumulated in the environment, raising concerns about their bioaccumulation, toxicity and mobility. Adsorption, particularly using activated carbon and ion exchange resins, is a suitable technique for PFAS removal from contaminated water. This study evaluates the sorption efficiency of granular and powdered activated carbon and two ion exchange resins to identify the most effective materials for remediation. All tested sorbents showed great performance, however Amberlite IRA 402, and powdered activated carbon K/B were the most efficient. Based on the isotherm models used, it is suggested that physisorption is a dominant process, where the multilayer adsorption on a heterogeneous surface is being favoured.